Revision of the genus Peltonotus Burmeister (Coleoptera: Scarabaeidae: Dynastinae) from Southeastern Asia - Jameson, Mary Liz; Wada, Kaoru (Zootaxa, 2004)
The genus Peltonotus Burmeister (Coleoptera: Scarabaeidae: Dynastinae) includes 19 species that are distributed throughout Southeastern Asia. We describe ten new species of Peltonotus: P. adelphosimilis, P. deltomentum, P. fujiokai, P. gracilipodus, P. kyojinus, P. nethis, P. podocrassus, P. silvanus, P. sisyrus, and P. suehirogarus. We synonymize two names: P. morio sawaii Miyake with P. morio Burmeister and P. sakaii Miyake & Yamaya with P. similis Arrow. Lectotypes are designated for the following species: P. malayensis Arrow, P. nasutus Arrow, and P. similis Arrow. A neotype is designated for P. morio Burmeister. The name P. peninsularis Miyake was not validly described and is an unavailable name. The genus Subpeltonotus Ghai et al. is synonymized with the genus Parastasia Westwood (Scarabaeidae: Rutelinae). We discuss the contentious nomenclatural history of the genus which was historically placed in the Dynastinae (tribe Cyclocephalini) and the Rutelinae (tribe Rutelini or Peltonotini). We discuss characters that support the monophyly of the genus Peltonotus, comment on the natural history and distribution of species in the genus, and provide a key to species.